Implementation of the banking dynamics model using a system of deterministic differential equations - Vincent, Aloysius; Sumarti, Novriana (Frontiers in Applied Mathematics and Statistics, 2025)
IntroductionThis study discusses modeling the interaction among components of a bank’s balance sheet, consisting of deposit, loan, and equity, as a useful tool for analyzing risk conditions arising from factors such as non-performing loans (NPSLs) and deposit withdrawals.MethodsThe model utilizes a deterministic differential equation system based on a modified logistic growth model.ResultsWhen applied to data of selected banks in Indonesia under certain assumptions, the model effectively describes the growth of their balance sheets.DiscussionOur findings indicate that banks with higher core capital do not necessarily exhibit more stable equilibrium than those with lower core capital. Additionally, the equity equilibrium does not show a consistent pattern among banks with varying levels of core capital.